UPAYA GURU DALAM MENGATASI KESULITAN SISWA PADA MAHĀRAH KALĀM (KETERAMPILAN BERBICARA) MELALUI LATIHAN MUHADATSAH (PERCAKAPAN) DI KELAS IX MTS AL-WASLIYAH TEMBUNG DELI SERDANG-SUMATERA UTARA - Bebi Khairani; Devi Khumairah Hayati; M Sony Farid; Syah Umar Hazrian; Sahkholid Nasution (Yayasan Haiah Nusratul Islam, 2024)
One of the problems in learning Arabic comes from the mahārah kalām side. Based on observations made by researchers, the problem encountered in the research field was that there were difficulties among class IX students in mahārah kalām. Some of the difficulties are difficulty in pronouncing the makharijul letters, hesitation in reading the hiwar and no variation in tone in reading the hiwar. The aim of this research is to provide a solution to the problems of mahārah kalām class IX students through the application of muhadtsah training. The method used in this research is a qualitative method with a descriptive approach. The data collection techniques used are through the stages of interviews, observations and tests. The data analysis technique used is the Miles Huberman model. The results of the research show that muhadtsah training has an important role in supporting the mahārah kalām abilities of class IX students, this is because in its implementation it teaches students slowly and repeatedly so that habituation and understanding emerge as well as students' ability to read Arabic conversation texts or translate Arabic conversations.